Parathyroid hormone is related to QT interval independent of serum calcium in patients with coronary artery disease. Issue 2 (26th September 2017) - Palmeri, Nicholas O.; Davidson, Karina W.; Whang, William; Kronish, Ian M.; Edmondson, Donald; Walker, Marcella D.
Abstract : Background: Elevated serum parathyroid hormone (PTH) is associated with increased risk of cardiovascular death, including sudden cardiac death, in patients with and without parathyroid disease. In small studies, PTH levels have been associated with changes in cardiac conduction and repolarization. Changes in the corrected QT interval (QTc) in particular are thought to be mediated by the effect of PTH on serum calcium. There is limited evidence to suggest PTH may affect cardiac physiology independent of its effects on serum calcium, but there is even less data linking PTH to changes in electrical conduction and repolarization independent of serum calcium. Methods: ECG data were examined from the PULSE database—an observational cohort study designed to examine depression after acute coronary syndromes (ACS) at a single, urban American medical center. In all, 407 patients had PTH and ECG data for analysis. Results: The QTc was longer in patients with elevated PTH levels compared with those without elevated PTH levels (451 ± 38.6 ms vs. 435 ± 29.8 ms; p < .001). The difference remained statistically significant after controlling for calcium, vitamin D, and estimated glomerular filtration rate ( p = .007). Inclusion of left ventricular ejection fraction in the model attenuated the association ( p = .054), suggesting that this finding may be partly driven by changes in cardiac structure. Conclusions: In one of the largest series to examine PTH, calcium, and QT changes, we found that elevated PTH is associated with longer corrected QT interval independent of serum calcium concentration in ACS survivors.